Simulation of mercury distribution in natural gas processes - Garofalo, Verdiana (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ). Εργαστήριο Θερμοδυναμικής και Φαινομένων Μεταφοράς, 2018)
Mercury is a trace component that can be found in all fossil fuels and it poses a considerable risk in natural gas processes. The presence of mercury in crude oil and natural gas varies in each stage of extraction, refining and transportation process because it distributes unequally among the vapor, condensate and aqueous phase as a function of pressure and temperature. Mercury causes a wide range of problems in refineries, e.g. equipment degradation, toxic waste generation, serious health impacts and poisoning of catalysts. This is due to its toxicity and its corrosive properties. The amount of mercury in crude oil and natural gas depends on its origins. However, its concentration usually ranges from 1 to 1000 ppb. Prior to mercury removal, the knowledge of its distribution in the different phases during the separations is necessary. In un-drilled reservoirs the solubility of elemental mercury in the various phases is given by the vapor-liquid-liquid equilibrium. During the drilling process, mercury emerges on the surface with petroleum and is probably redistributed to the various phases due to temperature and pressure changes. Both the fact that mercury exists at very low concentrations in fossil fuels and can cause major accidents in the natural gas industry, leads to the need of thermodynamic models that can accurately predict the distribution of mercury. The aim of this Diploma thesis is to evaluate two widely used cubic equations of state (EoS) coupled with different expressions for attractive parameter and mixing rules, i.e. SRK-Twu EoS and UMR-PRU EoS-GE model for simulating a natural gas processing plant and compare the results obtained for mercury partitioning in various streams. To this purpose, a review of the literature was conducted about mercury, its physical and chemical properties, its species, the most common forms of mercury found in oil & gas, its partitioning in the different compounds and also the reactions in which mercury participates. Afterwards, the SRK-Twu model and the UMR-PRU one, were implemented in the simulation of a real gas processing plant, developed in UniSim and in Aspen HYSYS, in order to compare their tendency to distribute mercury in the different phases during separation. The results showed that mercury is almost equally distributed in the vapor and liquid phase with some differences between the models. In particular, it was seen that UMR-PRU predicts a higher recovery of mercury in the export gas. Finally, a sensitivity analysis was made by changing the composition of the inlet feed (mercury, water and C7+ concentration) and some operating conditions, i.e. temperature and pressure, in the first three-phase separator. Thus, the new partitioning of mercury between the different phases was checked for both thermodynamic models. In addition, since the fluid under study is a multicomponent system, the distributions of the other components in the outlet streams were also investigated.